2006
DOI: 10.2478/s11658-006-0022-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of the human carbonyl reductase 2 gene HCR2 in hepatocellular carcinoma

Abstract: Altered gene expression was associated with the induction and maintenance of hepatocellular carcinoma (HCC). To determine the significance of HCR2 in HCC, here we compare the expression levels of HCR2 in carcinoma and in paired non-carcinoma tissues using semiquantitative reverse-transcription polymerase chain reaction (RT-PCR), Western blot analysis, and immunohistochemical staining. The expression ratio (ER) of HCR2 between the tumor and paired tumor-free tissues was calculated for each case and the data was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…Different studies showed that a decreased expression of HCR2 in HCC tissues contributes to cancer growth because it increases the cellular damage induced by ROS and other carcinogens [131]. …”
Section: Serum Markersmentioning
confidence: 99%
“…Different studies showed that a decreased expression of HCR2 in HCC tissues contributes to cancer growth because it increases the cellular damage induced by ROS and other carcinogens [131]. …”
Section: Serum Markersmentioning
confidence: 99%
“…Despite this limited information, the strikingly different expression pattern of DCXR in prostate cancer versus melanoma and liver cancer implies a highly tissue‐specific regulation. While an increased DCXR level has been detected in prostate cancer (Cho‐Vega et al , 2007 a ), in melanoma (Cho‐Vega et al , 2007 b ) and in hepatocellular carcinoma (HCC) DCXR was down‐regulated (Liu et al , ). In 58% of analyzed HCC cases from Chinese patients a reduced level of DCXR mRNA (in this study called human carbonyl reductase 2 or HCR2) was observed.…”
Section: Dcxr and Disease – The Multifunctional Nature Of Dcxrmentioning
confidence: 99%
“…Therefore, the decreased expression of HCR2 in HCC tissues contributes to cancer growth because it increases the cellular damage induced by ROS and other carcinogens. The HCR2 levels are inversely correlated to the pathological grading of HCC: lower HCR2 expression is detected in advanced lesions [51].…”
Section: Human Carbonyl Reductasementioning
confidence: 99%